Au Nanoparticles Modified with Pt, Ru and SnO2 as Electrocatalysts for Ethanol Oxidation Reaction in Acids. Issue 14 (12th June 2020) - Siddharth, Kumar; Xing, Zelong; Xiao, Fei; Zhu, Shangqian; Zhang, Lili; Pan, Feng; Shao, Minhua
Abstract: The anodic reaction in direct ethanol fuel cells (DEFCs), ethanol oxidation reaction (EOR) faces challenges, such as incomplete electrooxidation of ethanol and high cost of the most efficient electrocatalyst, Pt in acidic media at low temperature. In this study, core‐shell electrocatalysts with an Au core and Pt‐based shell (Au@Pt) are developed. The Au core size and Pt shell thickness play an important role in the EOR activity. The Au size of 2.8 nm and one layer of Pt provide the most optimized performance, having 6 times higher peak current density in contrast to commercial Pt/C. SnO2 as a support also enhances the EOR activity of Au@Pt by 1.73 times. Further modifying the Pt shell with Ru atoms achieve the highest EOR current density that is 15 and 2.5 times of Pt/C and Au@Pt. Our results suggest the importance of surface modification in rational design of advanced electrocatalysts. Abstract : Au@Pt core‐shell electrocatalysts are designed for ethanol oxidation reaction with optimized Au core size and Pt shell thickness, improving the peak current density six times as compared to commercial Pt/C. SnO2 as a support and Ru surface modification further enhances the activity.